A GPS-Based System Design for the Recognition and Tracking of Moving Targets - (:unkn) unknown (IEEE, 2009)
This study aimed to develop a software to enable recognition of moving objects and detection of their orbits by processing the images obtained through a camera. The secondary objective was to design a GPS-based mobile robot which tracks moving objects.
Keywords: target recognition; target tracking; mobile robot; adaptive algorithm